History of brazilian thermalism - Untura Filho, Marcos (Anales de Hidrología Médica, 2012)
This paper includes the history of Brazilian thermalism since the time it was a Portuguese colony until nowadays. One can establish four distinct periods: when it was a Portuguese colony (during this period these places were ignored or even hidden); during the empire when the governors used to go to these places promoting them with their sole presence in these thermal centers; their decline following World War II due to the increasing use of drugs; and the present revival covered by new legislations and with the collaboration from foreign educational centers.